EFFECT OFWHATSAPP USAGE ON PRE-SERVICETEACHERS’ LEARNING OUTCOMES IN BASIC GENERAL MATHEMATICS IN COLLEGES OF EDUCATION, OYO, OYO STATE (Unilorin Journal of Lifelong Education, 2025)
Pre-service teachers’ performances in Basic General Mathematics over the years have not been encouraging even as the course is a core course at all levels in Colleges of Education. This may be due to many factors such as, students’ attitude, use of appropriate learning strategy and other factors. This study examined the effects of WhatsApp Usage on Preservice teachers’ Basic General Mathematics Learning Outcomes in Colleges of Education, in Oyo State. A quasi-experimental research design was adopted and the population of the study comprised all 1601 pre-service year two teachers in the two Colleges of Education selected, while simple sampling technique was used to select190 samples for the study. Analysis of Covariance (ANCOVA) was used to analyse the hypotheses at 0.05 level of significance. Basic General Mathematics Achievement Test (BGMAT) and Pre-service Teachers’ Attitude Questionnaire (PTAQ) was the tools used for data collection. A reliability index of 0.76 for BGMAT using split-half reliability method and reliability coefficient of 0.88 for PTAQ using cronbach alpha . It was revealed from the results that, there was a significant main effect of WhatsApp Usage on pre-service teachers’ academics achievement (F (1, 152) = 5.565, p <0.05) and attitude (F (1, 152) = 315.342, p <0.05) in Basic General Mathematics in Colleges of Education in Oyo State, It was concluded that WhatsApp Usage improved pre-service teachers’ achievement and attitude toward Basic General Mathematics in Colleges of Education in Oyo State.